2014
DOI: 10.1039/c4cc00086b
|View full text |Cite
|
Sign up to set email alerts
|

The influence of chloride impurities on Pt/C fuel cell catalyst corrosion

Abstract: Potentiodynamic Pt/C fuel cell catalyst corrosion has been studied as a function of chloride concentration with an electrochemical flow cell (EFC) coupled with highly sensitive ICP-MS. The Pt corrosion mechanism changes significantly: the anodic corrosion is much enhanced compared to the cathodic corrosion that prevails in electrolytes without Cl(-).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 18 publications
7
74
0
Order By: Relevance
“…Pt + PtCl 6 2− + 2Cl − → 2PtCl 4 2− [13] In the cathodic scan, Pt 4+ dissolution continues until 1.2 V, as represented by the I C in Fig. 10b.…”
Section: Resultsmentioning
confidence: 97%
“…Pt + PtCl 6 2− + 2Cl − → 2PtCl 4 2− [13] In the cathodic scan, Pt 4+ dissolution continues until 1.2 V, as represented by the I C in Fig. 10b.…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, our approach stands on the following crucial concepts: (i) transient platinum dissolution is an aggressive corrosion process that occurs upon oxidation and reduction of a Pt surface, also referred to as anodic and cathodic Pt dissolution2122. Note that the dissolution at constant electrode potentials above the Pt dissolution onset, which could be compared with soaking in acid, is much lower compared with the transient process232425; (ii) the rate of Pt transient dissolution is accelerated by the presence of chlorides and other halides. We show that, by slowing the process of Pt passivation, chlorides dramatically increase Pt dissolution during anodic and cathodic potential excursions and, at the same time, stabilize Pt ions in the solution2526; and (iii) the presence of dissolved CO gas increases Pt cathodic dissolution due to strong Pt–CO interaction, which physically prevents any potential Pt redeposition27 that may occur when CO (or some other reducing species such as H 2 ) oxidation potential gets below Pt depostition potential.…”
mentioning
confidence: 99%
“…[17][18][19][20][21][22][23] In a series of papers, Mayrhofer and co-workers showed that during potential cycling with UPL higher than 1.1 V, greater Pt dissolution occurs during the cathodic scan than during the anodic scan. 17,21,22 The amount of Pt dissolved during the cathodic scan increased with increasing UPL as well as with decreasing scan rate and occurred at potentials below 1 V in the cathodic scan.…”
mentioning
confidence: 99%